NURSES' BEREAVEMENT NEEDS AND ATTITUDES TOWARDS PATIENT DEATH: A QUALITATIVE DESCRIPTIVE STUDY OF NURSES IN A DIALYSIS UNIT. Issue 2 (8th January 2016) - Tranter, Shelley; Josland, Elizabeth; Turner, Kylie
SUMMARY: Background: Dialysis nurses have a unique relationship with their patients and often require bereavement support should a patient death occur. This study was conducted in 2014 and aimed to explore the attitudes of dialysis nurses to death and dying and to identify suitable bereavement strategies following a death of a patient. Methods: A purposeful, convenience sample of all nurses employed in the dialysis service completed a demographic profile and The Death Attitudes Profile Revisited (DAP_R) survey. Results: There were 52 responses to the survey (98% response rate). The mean age of the participants was 45 years ± 8.0 years; 87% had >10 years nursing experience. Nurses suggest that debriefing and the use of a counsellor would support them in their grieving process while new graduate nurses appear to require extra support following a patient death. Analysis of the death attitude profile‐revised (DAP‐R) showed significant relationships between fear of death/death avoidance as well as fear of death/neutral acceptance. Spirituality and religion correlate strongly with 'Approach Acceptance' in this study group. Forty‐four percent people who 'approach acceptance' of death can be explained by the strength of religious beliefs. Conclusions: Many dialysis nurses appear to have strong religious or spiritual belief systems and this contributes to their acceptance of death, although there also appears to be a degree of death avoidance. The study has highlighted the need to provide adequate bereavement support for dialysis nurses.